Increasing Performance through Interpersonal Communication and Personality of Firefighters Officer in Depok City, Indonesia - Sutrisno, Slamet; Yusnita , Nancy; Sunaryo, Widodo (Eastasouth Institute, 2024)
This study aims to find efforts increasing officer performance, through interpersonal communication, and personality. The population in this study was fire officers in the Depok City Indonesia area with a total of 161 fire officers. The sampling technique used proportional random sampling with the slovin formula with an error margin of 5%, the sample size was 115 fire officers. The data analysis method used in this research is path analysis. This research resulted in the conclusion 1) There is a positive direct effect of interpersonal communication on officer performance. 2) There is a positive direct effect of personality on officer performance. The most dominant variables in improving officer performance are interpersonal communication.